Effect of zinc supplementation on production performance and udder health of peri-parturient karan fries cows under heat stress condition - Kumar, Nishant; Patel, Brijesh; Singh, S V (Indian Journal of Dairy Science, 2017)
Present study was carried out to evaluate the effect of zinc (Zn) supplementation on production performance and udder health of peri-parturient KF (Karan Fries) cows during heat stress condition. 18 peri-parturient Karan Fries cows were divided into three groups namely control, T1 and T2 having six cows in each group. Control group was fed basal diet alone, however T1 and T2 groups were fed with 80 ppm and 120 ppm Zn, respectively along with basal diet from 45 days pre-partum to 45 days post partum. Results showed that plasma Zn level was significantly (P<0.05) higher in supplemented group than control. Milk and fat-corrected milk yield in Karan Fries cows were significantly (p<0.05) affected Zn supplementation. Dry matter intakes (DMI) and composition milk were not significantly different between control and treatments. However, Karan Fries cows that received supplemental Zn were having lower (p<0.05) somatic cell count as compared to control. It was concluded that Zn supplementation in diet of peri-parturient Karan Fries cows result in significantly increased milk yield and lower somatic cell count. However, milk composition was not affected by supplemental Zn.Â